When mother tongue shapes target language prosody: Suprasegmental transfer from Banjarese to English - Fadillah, Ridha; Ridha, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the influence of Banjarese prosodic features on English suprasegmental performance (stress, rhythm, and intonation) among undergraduate EFL students at UIN Antasari Banjarmasin. While these features are critical for intelligibility, they remain under-addressed in EFL instruction. Using a qualitative approach, seven native Banjarese speakers were purposively selected and engaged in semi-structured interviews that elicited both metalinguistic reflections and spoken English samples. Data were transcribed and subjected to content analysis. Results indicate systematic L1 transfer manifesting in three primary patterns: (1) a tendency toward final-syllable stress placement, (2) reduced intonational variation, and (3) a syllable-timed rhythmic structure. These prosodic transfers were found to compromise speech naturalness and intelligibility. Participants reported employing compensatory strategies—including auditory imitation, self-monitoring, and corrective feedback—to mitigate these challenges. The study contributes to second language acquisition theory by documenting suprasegmental transfer in a previously underexplored linguistic community. It further argues for the explicit integration of suprasegmental instruction within Indonesian higher education curricula. Pedagogical recommendations include rhythm-focused drilling, prosodic shadowing tasks, and metacognitive reflection to enhance phonological awareness. The research concludes that fostering prosodic competence is essential for developing communicative proficiency in multilingual EFL contexts.